Surgical outcomes of T4b oral cancers: assessment of prognostic factors and a need to re-evaluate the current staging system. Issue 2 (February 2023) - Rai, S.; Nandy, K.; Bhatt, S.; Patel, D.; Mithi, M.; Rathod, P.
Abstract: T4b oral cancer is a broad umbrella term for all advanced oral cancers, the prognosis of which varies drastically for disease of the same stage, according to the extent of the masticator space involvement. This was a retrospective observational study including all consecutive T4b oral squamous cell carcinoma patients treated surgically between January 2015 and January 2016 and followed up until January 2020. The disease was classified as upper disease or lower disease based on the anatomical location in relation to an imaginary plane passing through the base of the retromolar trigone. The prime objective was to evaluate overall survival and prognostic factors affecting overall survival. The projected 5-year overall and disease-free survival rates were 40.7% and 35.6%, respectively. The assessment of prognostic factors revealed that lower disease (lower anatomical subsites), bone invasion, and lymph nodal spread significantly affected survival. Patients with disease in an upper anatomical location without bone and nodal involvement can achieve fairly good survival (projected 5-year overall survival of 64.2%) when compared to the other subsets of patients. We propose a re-evaluation of the current staging system based on the prognostic features, so that all patients are not considered under a single stage, since their survival differs significantly.